2018
DOI: 10.1536/ihj.17-592
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Patients with Critical Limb Ischemia due to Arteriosclerosis Obliterans Who Did Not Undergo Arterial Reconstruction

Abstract: The prevalence of arteriosclerosis obliterans (ASO) and critical limb ischemia (CLI) is currently increasing, and arterial reconstruction is often attempted to salvage the limb. Some patients cannot undergo attempted revascularization because of contraindications, and they only receive conservative treatment. In this study, we investigate the comorbidities and survival rates of patients with CLI who receive conservative treatment. Thirty-five patients with CLI due to ASO, who had not undergone revascularizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…It has been proposed that the enzymatic activity of telomerase is primarily controlled by transcriptional regulation of TERT, as shown in our results at POD 3. In contrast, there are many reports that telomerase activity is regulated by several factors, such as ROS, exercise capacity and cellular stress related to the magnitude of ischemia, 32,40,41) which may affect TERT expression and telomerase activity in chronic ischemic conditions. We did not observe a positive correlation between telomerase activity and TERT expression in ischemic old mice at POD 21.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been proposed that the enzymatic activity of telomerase is primarily controlled by transcriptional regulation of TERT, as shown in our results at POD 3. In contrast, there are many reports that telomerase activity is regulated by several factors, such as ROS, exercise capacity and cellular stress related to the magnitude of ischemia, 32,40,41) which may affect TERT expression and telomerase activity in chronic ischemic conditions. We did not observe a positive correlation between telomerase activity and TERT expression in ischemic old mice at POD 21.…”
Section: Discussionmentioning
confidence: 93%
“…Critical limb ischemia is an end-stage of PAD and is associated with a high risk of lower limb loss. 32) Therefore, new treatments that rescue the ischemic limb for patients of PAD are necessary. Telomerase is closely related with cellular senescence and may be a potential anti-aging therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some cases of CLI that exist but do not advance despite not receiving any treatment. 3) Conversely, some wounds end up being subjected to lower limb amputation even when the degree of ischemia is mild. Thus, the appropriateness of making decisions on therapeutic strategies that are solely based on the degree of ischemia is now being questioned.…”
Section: Definition and Diagnosis Of Severe Foot Lesionsmentioning
confidence: 99%
“… 2010 ; Akagi et al. 2018 ; Halliday and Bax 2018 ). Epidemiological surveys have reported that currently approximately 200,000,000 patients are suffering from ASO worldwide (Halliday and Bax 2018 ; Zhang R et al.…”
Section: Introductionmentioning
confidence: 99%